Receiving advice from a health professional and action taken to reduce dietary sodium intake among adults. Issue 12 (11th August 2021) - Woodruff, Rebecca C; Overwyk, Katherine J; Cogswell, Mary E; Fang, Jing; Jackson, Sandra L
Abstract: Objective: Population reductions in Na intake could prevent hypertension, and current guidelines recommend that clinicians advise patients to reduce intake. This study aimed to estimate the prevalence of taking action and receiving advice from a health professional to reduce Na intake in ten US jurisdictions, including the first-ever data in New York state and Guam. Design: Weighted prevalence and 95 % CI overall and by location, demographic group, health status and receipt of provider advice using self-reported data from the 2017 Behavioral Risk Factor Surveillance System optional Na module. Setting: Seven states, the District of Columbia, Puerto Rico and Guam. Participants: Adults aged ≥ 18 years. Results: Overall, 53·6 % (95 % CI 52·7, 54·5) of adults reported taking action to reduce Na intake, including 54·8 % (95 % CI 52·8, 56·7) in New York and 61·2 % (95 % CI 57·6, 64·7) in Guam. Prevalence varied by demographic and health characteristic and was higher among adults who reported having hypertension (72·5 %; 95 % CI 71·2, 73·7) v . those who did not report having hypertension (43·9 %; 95 % CI 42·7, 45·0). Among those who reported receiving Na reduction advice from a health professional, 82·6 % (95 % CI 81·3, 83·9) reported action v . 44·4 % (95 % CI 43·4, 45·5) among those who did not receive advice. However, only 24·0 % (95 % CI 23·3, 24·7) of adults reported receiving advice from a health professional to reduce Na intake. Conclusions: The majority of adults report taking action to reduce Na intake. Results highlight an opportunity to increase Na reduction advice from health professionals during clinical visits to better align with existing guidelines.